Pragmatic Validation of Home Portable Sleep Monitor for diagnosing Obstructive Sleep Apnea in a non-referred population: The ELSA-Brasil study - Aline N. Aielo; Ronaldo B. Santos; Wagner A. Silva; Barbara K. Parise; Silvana P. Souza; Lorenna F. Cunha; Soraya Giatti; Paulo A. Lotufo; Isabela M. Bensenor; Luciano F. Drager (Sleep Science, 2019)
Objective: Polygraphy (PG) is an attractive alternative for diagnosing obstructive sleep apnea (OSA) in patients with high pre-test probability. However, several patients may not present typical symptoms. In this scenario, it is unclear the performance of PG for diagnosing OSA in nonreferred populations to sleep laboratories. Methods: Data from participants of the ELSA-Brasil cohort were used for this analysis. We performed an overnight home PG (Embletta GoldTM) synchronized with a wrist actigraphy (Actiwatch model 2TM). The validation strategy comprised three scorings from each participant: 1) Original scoring (PG): Routine scoring using data from the exclamation button mark to define “analysis start” and “analysis stop”; 2) Scoring using actigraphy data (PG+actigraphy): total sleep time defined by the actigraphy data; 3) Scoring using diaries (PG+diary): “analysis start” and “analysis stop” based on the diaries. Bland-Altman plots were generated to assess the agreements (Kappa) between each scoring strategy. Results: A total of 300 participants were included in the final analysis (45% males, mean age: 48±8 years). The frequency of OSA using the PG score was 27.3%. Despite small differences in the OSA severity index, we obtained a high concordance of AHI comparing the PG vs. PG+actigraphy (Kappa: 0.95) as well as PG+diary vs. PG+actigraphy (Kappa: 0.96). No significant changes in the OSA classification (mild, moderate and severe) were observed in the 3 protocols. Conclusion: Using a pragmatic approach to address OSA at home, our results suggest that PG is a useful tool for OSA diagnosis even in subjects not referred to sleep studies.